Light in The Shadow: A Screenplay on Self-Determination in Facing Quarter-Life Challenges - Tjio, Ryoko Aristo Kurnia; Liem Satya Limanta; Bernadeth Febyola Linando (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
This study aims to examine the role of self-determination in navigating the quarter-life crisis faced by young adults. The protagonist, Maya, conflicts with extrinsic pressures from society and her mother's expectations regarding her career choice. Through a mystical encounter with traditional Indonesian shadow puppets, Maya is empowered to exercise self-determination by pursuing her intrinsic passions despite external opposition. The narrative centers on Maya's transformative journey of self-discovery, where she reconciles her autonomous aspirations with controlling extrinsic forces. Ultimately, by harnessing self-determination, Maya overcomes challenges to showcase her authentic self. The screenplay illuminates self-determination's vital role in conquering quarter-life obstacles, cultivating intrinsic motivation, authenticity, and resilience in shaping one's life path while honoring cultural heritage.